2018
DOI: 10.18502/ijhoscr.v12i4.109
|View full text |Cite
|
Sign up to set email alerts
|

Association between TLR2 and TLR4 Expression and Response to Induction Therapy in Acute Myeloid Leukemia Patients

Abstract: Background: Toll-like receptors (TLRs) are a family of transmembrane pattern-recognition receptors that play a crucial role in the realization of innate and adaptive immune response. TLRs may play a role in tumor development and growth because of expression or up-regulation of functional TLRs in some tumors and tumor cell lines. The participation of TLRs in the pathogenesis of acute myeloid leukemia (AML) remains unspecified. This study aimed to investigate the effect of TLR2 and TLR4 expression in peripheral … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 45 publications
1
12
0
Order By: Relevance
“…As summarized in the Introduction, previous studies of TLRs in AML have mainly focused on cell proliferation and survival, and several of these studies were mainly based on the use of cell lines [12,13,14,15,16,17]. In the present study, we therefore focused on detection of functional receptors and mRNA expression of TLRs and proteins downstream in the signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As summarized in the Introduction, previous studies of TLRs in AML have mainly focused on cell proliferation and survival, and several of these studies were mainly based on the use of cell lines [12,13,14,15,16,17]. In the present study, we therefore focused on detection of functional receptors and mRNA expression of TLRs and proteins downstream in the signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Of note, we did not detect TLR2 to be differentially expressed within our cohort. High mRNA expression of this particular receptor was in a previous study linked both with shorter overall survival and less response towards treatment [13], whereas another study reported reduced TLR2 mRNA levels at remission, but could not link TLR2 expression at diagnosis with patient survival [12].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, Toll-like receptors (TLRs) play an important role in the immune response. It has been showed that after induction chemotherapy, the mRNA expression of TLR2 was significantly lower as compared to before treatment [56]. There are many other costimulatory domains, such as Dap10 costimulatory domains, 2B4 costimulatory domains, GITR domains, CD150 signaling lymphocytic activation molecule (SLAM), a 150-kDa protein termed as M150.…”
Section: Construction Of a Carmentioning
confidence: 99%
“…The significance of IRGs in AML progression and immunotherapeutics have been reported previously (22,23). However, to the best of our knowledge, no comprehensive, genome-wide profiling analysis of the prognostic significance of all IRGs in NK-AML has so far been performed.…”
Section: Discussionmentioning
confidence: 99%